Paciente de sexo masculino de 65 años de edad que presenta diabetes mellitus tipo ii y sobrepeso - Carpio Pino, Silvana Mayerli (2020)
In the present clinical case, a 65-year-old male patient was diagnosed with type 2 diabetes mellitus 15 years ago. He has not had the proper care both at the pharmacological level and in his diet, so he goes to the doctor for general discomfort, headaches, nausea and vomiting. Therefore, the main objective is to control the patient's glucose levels and ensure that their body mass index reaches the normal range. The nutritional evaluation was performed out detailing the anthropometric, biochemical, clinical and dietary assessment. Through this it was possible to identify that the patient is overweight with a BMI of 29.4 kg / m2. The patient also has a high percentage of body fat. High levels of fasting glycemia were reflected in the biochemical data and also showed that cholesterol and triglyceride levels were high, making the presence of dyslipidemia known, clinical signs showed signs and symptoms of diabetes, and in the dietary assessment it was known that the patient has an inadequate diet, consuming foods with excess calories, carbohydrates, lipids and a small amount of protein. When identifying the nutritional status of the patient, an appropriate nutritional intervention was performed, it consisted of an individualized dietary plan according to the patient's pathology, which provides the necessary caloric requirements, adequate food and avoids the consumption of those foods that should not be ingested. Subsequently, the necessary follow-up was carried out where it was observed that his body mass index changed to 27.9 kg / m2 entering a normal level according to his age group, his chemical values were also decreasing and in those there is the glycemia that reached 106 mg / dl thus obtaining compliance with the objective set for the case.